Management of labour productivity at the enterprises of the agricultural industry of Ukraine - Bukharina, Liudmyla; Shyshkin, Viktor; Onyshchenko, Oksana (Management and Entrepreneurship: Trends of Development, 2021)
The agro-industrial complex is one of the main budget-forming sectors of the national economy of Ukraine; agribusiness opens up prospects for leadership for our state in the world market. Therefore, an important step for unlocking the export potential of Ukrainian agricultural products is to analyse urgent problems and find ways to strengthen Ukraine's competitive positions in the world market, including by increasing labour productivity, which is one of the most important criteria for assessing the performance of any economic system. The article aims to study the current level of labour productivity in the national agro-industrial sector and to find ways to increase it by eliminating the main barriers to the development of the agro-industrial complex of Ukraine. The basic principles of the research are systematic and comparative methods, institutional and structural-functional approaches have been used. The research results highlight the reasons for low productivity and propose priority areas of state policy for the development of the national agro-industrial complex.JEL Classification: D24, J43, O13.